Analysis of Phytoconstituents and Biological Activities of Different Parts of Mahonia nepalensis and Berberis aristata - Thusa, Rojeena; Mulmi, Sushika (Nepal Journal of Biotechnology, 2017)
The phytochemicals and biological activities of extracts from leaves and stem of Mahonia nepalensis and Berberis aristata were carried out. Phytochemical screening showed the presence of alkaloids, steroids, polyphenols, quinones, glycoside, flavonoid, terpenoid and cardiac glycoside in the hexane, ethyl acetate and methanol extracts of leaf and stem of these two plants. The column chromatography of methanol extract of stem of Mahonia nepalensis resulted in isolation of four pure compounds MN1, MN2, MN3 and MN4. Out of four isolated compounds, two were identified as MN1:b- sitosterol and MN2: Berberine by comparison of melting point, Co-TLC, IR and UV spectra of authentic sample. Potent pharmacological activity of Mahonia nepalensis and Berberis aristata were revealed from antimicrobial activity and brine shrimp bioassay. Methanol extracts of stem of Mahonia nepalensis and Berberis aristata showed significant zone of inhibition of 18 mm and 21 mm respectively against the Staphylococcus aureus. Methanol extract of Berberis aristata were comparatively little stronger against Staphylococcus aureus than methanol extract of Mahonia nepalensis. LC50 values (μg/ml) of methanol extracts of stem of Berberis aristata and Mahonia nepalensis were found to be 8.058x10-4 and 8.3 whereas methanol extracts of leaf of Mahonia nepalensis and Berberis aristata were 389.04 and 1303.166 respectively. Nepal Journal of Biotechnology. Dec . 2 0 1 7 Vol. 5, No. 1: 5-13